2001
DOI: 10.2174/0929867013373787
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase: A Target for Antiproliferative and Antiprotozoal Agents

Abstract: Histone deacetylase (HDAC) and histone acetyltransferase (HAT) are enzymes that influence transcription by selectively deacetylating or acetylating the eta-amino groups of lysines located near the amino termini of core histone proteins. It is well-established that in transcriptionally active chromatin, histones generally are hyperacetylated and, conversely, hypoacetylated histones are coincident with silenced chromatin. Revived interest in these enzymatic pathways and how they modulate eukaryotic transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 92 publications
1
93
0
1
Order By: Relevance
“…Yeast GCN5 is a subunit of two high molecular mass histone acetylase complexes that are recruited to the promoter by interaction with transcription factors (for a review see [26]). Interestingly drugs that inhibit histone deacetylases, such as apicidin, show a strong antiprotozoal activity, suggesting that a fine-tuning between histone acetylation and deacetylation is important for the survival of the parasite [27,28]. In this context, recent studies have revealed several hints that chromatin remodelling plays a role in regulation of antigenic variation in P. falciparum.…”
Section: Genome Chromatin Structure and Remodelling Factorsmentioning
confidence: 99%
“…Yeast GCN5 is a subunit of two high molecular mass histone acetylase complexes that are recruited to the promoter by interaction with transcription factors (for a review see [26]). Interestingly drugs that inhibit histone deacetylases, such as apicidin, show a strong antiprotozoal activity, suggesting that a fine-tuning between histone acetylation and deacetylation is important for the survival of the parasite [27,28]. In this context, recent studies have revealed several hints that chromatin remodelling plays a role in regulation of antigenic variation in P. falciparum.…”
Section: Genome Chromatin Structure and Remodelling Factorsmentioning
confidence: 99%
“…SCFAs induce cell cycle arrest, differentiation and apoptosis in cancer cells, several also have anti-inflammatory activities, and a number have progressed to clinical trials. These agents, which include NaBu and (R)-trichostatin A (TSA), have displayed anti-proliferative and differentiating activity in a wide variety of cancers (7)(8)(9). Research has shown that NaBu induces tumor cell apoptosis in colon, breast, esophageal and prostate cancer (10).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic balance of DNA acetylation levels in cells, modulated by histone deacetylase (HDAC) and histone acetyltransferases (HATs), is crucial for regulating chromatin structure and transcriptional dysregulation of genes that are implicated in controlling either cell cycle progression or pathways regulating cell differentiation and/or apoptosis (1)(2)(3)(4)(5). Evidence has shown that this epigenetic marking system is associated with inappropriate gene expression in many forms of cancer (3,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that this epigenetic marking system is associated with inappropriate gene expression in many forms of cancer (3,6,7). Encouraged by the finding that inhibition of HDAC induces cancer cell apoptosis (8,9), inhibitors of HDAC have been developed as a potent and specific strategy for the treatment of solid tumors and hematological malignancies (1,2,(10)(11)(12). Several classes of HDAC inhibitors have been developed including short-chain fatty acids, such as phenylbutyrate and valproic acid (10); various hydroxamic acid derivatives such, as SAHA and TSA (4,12,13); and cyclic tetrapeptides, such as depsipeptide (2,10,14).…”
Section: Introductionmentioning
confidence: 99%